Plan de negocios para la creación de la empresa procesadora y comercializadora de carnes bovinas maduras empacadas al vacío en los estratos socio económicos 3, 4, 5 y 6 en Armenia, Quíndio “Carnes Gourmeat” (2014)
This research is motivated to design a business plan as thesis option, in the first instance a short presentation on how the livestock sector and the meat chain in Colombia, especially in the department of Quindio, highlighting works is the town of Armenia then a technical analysis of the product at the regional and local market takes place, then a plan relative to consumption and production control systems, legal and social analysis from the economic environment is presented. As students studying Business Administration, has been able to identify a business opportunity and enter the market for beef, given its importance to the regional and national economy, entering one of the most important economic sectors, with excellent projection as livestock, since the supply of such food products on the market is limited and does not meet the expectations and demands of the market. Finally, a financial analysis by which the profitability and expected growth of the company, in addition, an analysis of risks and intangibles on the market is designed projects , the comprehensive evaluation of the project, the financial structure , sensitivity , and language to be presented end a series of conclusions and recommendations on the feasibility study for the creation of processor and marketer mature Bovine Meat vacuum packed in the Socio Economic strata 3, 4 , 5 and 6 in Armenia, Quindio " provided" Carnes Gourmeat " project undertaken to qualify the title of Manager of Business at the University of Quindio